THE EFFECTIVENESS OF LEARNING COMMUNICATION TROUGH DIGITAL MEDIA - Romi Syahril; Azhar Hutomo; Robbikal Muntaha Meliala; Priatna Priatna (Sean Institute, 2023)
This study analyzes the effectiveness of learning communication trough digital media based on the theory of symbolic mediation communication. Qualitative research methods are used with a case study design to gain a deep understanding of the experiences of teachers and students in using digital media in learning. The results of the study show that the use of digital media in learning contributes positively to the effectiveness of communication between teachers and students. Symbols in digital media, such as pictures and videos, enrich students' understanding of learning concepts. Interaction and collaboration through digital media also increase student participation. However, there are some challenges that need to be overcome, such as distractions and technical difficulties that can interfere with effective communication.